1990
DOI: 10.1172/jci114571
|View full text |Cite
|
Sign up to set email alerts
|

Measles virus-substance P receptor interactions. Possible novel mechanism of viral fusion.

Abstract: Measles virus (MV) encodes the fusion protein (F) that mediates cell fusion and intercellular spread of the virus, and is homologous to the carboxy terminus of the neuropeptide substance P (SP). In addition, the oligopeptide Z-D-Phe-L-PheGly, also homologous to F and SP, inhibits MV fusion with target cells. These observations raise the question of whether MV uses the SP receptor (SPR) during a specific phase of its infectious cycle. In this report, we examine the structural and functional consequences of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Measles virus (MV) encodes the fusion protein (F), which mediates cell fusion and the intercellular spread of the virus and is homologous to the carboxy terminus of the SP (Harrowe et al 1990). In addition, the oligopeptide Z-D-Phe-L-Phe-Gly (Table 2), a homologous antagonist (peptide NK-1 receptor antagonist) to F and SP, inhibits MV fusion with target cells.…”
Section: Measles Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…Measles virus (MV) encodes the fusion protein (F), which mediates cell fusion and the intercellular spread of the virus and is homologous to the carboxy terminus of the SP (Harrowe et al 1990). In addition, the oligopeptide Z-D-Phe-L-Phe-Gly (Table 2), a homologous antagonist (peptide NK-1 receptor antagonist) to F and SP, inhibits MV fusion with target cells.…”
Section: Measles Virusmentioning
confidence: 99%
“…These observations raise the question of whether MV uses the NK-1 receptor during a specific phase of its infective cycle. Moreover, bound MV and SP have been shown to displace each other from target cells reciprocally (Harrowe et al 1990). In addition, anti-SP antisera inhibit the cellto-cell spread of MV, blocking MV fusion with target cells.…”
Section: Measles Virusmentioning
confidence: 99%
“…Notably, SPR apparently redistributes in T cells toward the VS, and, given its ability to support MV entry into T cells and cell-to-cell transmission in neurons, may play an active role in MV uptake (Fig. 6) (19,20,30). The similarity of the internal substance P FFG sequence with FIP and the N-terminal hydrophobic MV F1 fusion domain suggested it might, by interacting with the MV F protein, enhance fusion, which may well affect the sensitivity of this process to neutralizing antibodies (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of MV nucleocapsids and MV Hemagglutinin in the neuronal axonal processes suggest that MV spreads transneuronally (Rima & Duprex, 2005 for a review). In 1990 D.Payan and collaborators found that a lymphoblastoid cell line that constitutively express the neuropeptide, (substance P) receptor, neurokinin-1, facilitate MV fusion (Harrowe et al, 1990). M. Billeter and cols in slice cultures demonstrated neuron-to-neuron polarized spread of a recombinant autoflurescent MV (Ehrengruber et al, 2002).…”
Section: Sspe Onset Clinical Course and Pathogenesismentioning
confidence: 99%